Privacy and incongruence-focused disaggregation of water consumption data in real time. (2015) - Kalogridis, Georgios; Farnham, Tim; Wilcox, James; Faies, Mohammed
Abstract: While fixture-level disaggregation of water data has a number of applications in decision support systems, it also gives rise to data privacy risks. This paper presents a system of algorithms that identify and detect water activity events, and then analyse disag- gregated information to distinguish between privacy-sensitive behaviour and incongruent data due to technical faults or leakages. The process running in real-time is implemented within the Complex Event Processor (CEP) of WSO2 and the ICeWater project. Results provide insights of future directions in theoretical aspects of disaggregation, privacy and CEP system implementation.